Identification of the short-lived Santa Rosa geomagnetic excursion in lavas on Floreana Island (Galapagos) by ⁴⁰Ar/³⁹Ar geochronology - Balbas, Andrea; Koppers, Anthony A. P.; Kent, Dennis V.; Konrad, Kevin; Clark, Peter U. (Geological Society of America, 2016)
A set of closely related basaltic lava flows (supersite GA-X) on Floreana Island in the Galapagos Archipelago has a published record of an excursional or transitional direction (virtual geomagnetic pole located at 153.1°E, 54.2°S with α₉₅ = 5.0°) and a geomagnetic field strength (1.1 × 10²² Am²) that is only ∼14% of the strength of the modern magnetic field (7.8 × 10²² Am²). The very large age uncertainty of previous dating of a lava flow (G43) from this set, however, has prevented placing this event in the geomagnetic polarity time scale. Here we report highly reproducible and precise ⁴⁰Ar/³⁹Ar ages on the lava flow that indicate that the distinct geomagnetic excursion is 925.7 ± 4.6 ka (2σ; n = 6; mean square of weighted deviates = 1.23). This shows that this dramatic weakening of the geomagnetic field is associated with the Santa Rosa Excursion instead of the Matuyama-Brunhes polarity reversal. Our high-precision ⁴⁰Ar/³⁹Ar ages for Floreana provide evidence for the global significance of the Santa Rosa Excursion.